Accounting Conservatism: Gender Diversity Accounting Conservatism: Gender Diversity and Educational Background on the Board of and Educational Background on the Board of Directors and Commissioner - Banu Witono; Widowati Dian Permatasari; Dewita Puspawati (Riset Akuntansi dan Keuangan Indonesia, 2023)
This research aimed to analyze the effect of the board director’s characteristics and the board of commissioners toward accounting conservatism. The characteristics analyzed in this research were size, gender, and educational background that affect their behavior in dealing with issues related to accounting principles. This research will be conducted by analyzing all companies listed on the Indonesia Stock Exchange in 2017-2019 using SPSS. Data was analyzed as 112 data using multiple regression analysis. The results show that both size of directors and commissioner’s and women of board director and commissioners affect the accounting conservatism. However, the educational background of board directors and commissioners does not affect accounting conservatism.